Determination of Trace Elements in Coptis teeta and Soil by ICP-AES - Zhang, Ji; Zhang, Xue; Wang, Yuanzhong; Liu, Guizhou; Zhao, Yanli; Cai, Chuantao; Jin, Hang (Asian Journal of Chemistry, 2011)
The contents of Ca, Mg, Fe, Mn and Zn in Coptis teeta Wall. and soil from Yunnan province of China were determined by inductively coupled plasma atomic emission spectroscopy (ICPAES). The spike recoveries were between 97.7-107.4 % and the RSD were between 0.47-1.70 %. The order of the element contents was Fe > Ca > Mg > Mn > Zn in soil and Ca > Mg > Fe > Zn > Mn in rhizome of Coptis teeta and Mg > Ca > Fe > Mn > Zn in root of Coptis teeta. Ca-Fe had significantly positive correlation at the 0.05 level (r = 0.746) in soil and Ca-Mg, Ca-Fe, Ca- Mn, Ca-Zn, Mg-Fe, Mg-Mn, Mg-Zn, Fe-Mn, Fe-Zn, Mn-Zn at the 0.01 level (r = 0.824-0.991). Ca-Zn had significantly negative correlation at the 0.01 level (r = -0.870) in rhizome of Coptis teeta. Mn-Ca, Zn-Ca had significantly negative correlation at the 0.05 level (r = -0.771, -0.753) in root of Coptis teeta, whereas Zn-Mn had significantly positive correlation at 0.05 level (r = 0.786). Ca-Ca had significantly positive correlation at 0.01 level (r = 0.9117) between rhizome and root of Coptis teeta and Fe-Fe at 0.05 level (r = 0.693).